Evaluation of antibody serology to determine current helminth and Plasmodium falciparum infections in a co-endemic area in Southern Mozambique. - Rebeca Santano; Rocío Rubio; Berta Grau-Pujol; Valdemiro Escola; Osvaldo Muchisse; Inocência Cuamba; Marta Vidal; Gemma Ruiz-Olalla; Ruth Aguilar; Javier Gandasegui; Maria Demontis; Jose Carlos Jamine; et al. (PLoS Neglected Tropical Diseases)
Background Soil-transmitted helminths (STH), Schistosoma spp. and Plasmodium falciparum are parasites of major public health importance and co-endemic in many sub-Saharan African countries. Management of these infections requires detection and treatment of infected people and evaluation of large-scale measures implemented. Diagnostic tools are available but their low sensitivity, especially for low intensity helminth infections, leaves room for improvement. Antibody serology could be a useful approach thanks to its potential to detect both current infection and past exposure. Methodology We evaluated total IgE responses and specific-IgG levels to 9 antigens from STH, 2 from Schistosoma spp., and 16 from P. falciparum, as potential markers of current infection in a population of children and adults from Southern Mozambique (N = 715). Antibody responses were measured by quantitative suspension array Luminex technology and their performance was evaluated by ROC curve analysis using microscopic and molecular detection of infections as reference. Principal findings IgG against the combination of EXP1, AMA1 and MSP2 (P. falciparum) in children and NIE (Strongyloides stercoralis) in adults and children had the highest accuracies (AUC = 0.942 and AUC = 0.872, respectively) as markers of current infection. IgG against the combination of MEA and Sm25 (Schistosoma spp.) were also reliable markers of current infection (AUC = 0.779). In addition, IgG seropositivity against 20 out of the 27 antigens in the panel differentiated the seropositive endemic population from the non-endemic population, suggesting a possible role as markers of exposure although sensitivity could not be assessed. Conclusions We provided evidence for the utility of antibody serology to detect current infection with parasites causing tropical diseases in endemic populations. In addition, most of the markers have potential good specificity as markers of exposure. We also showed the feasibility of measuring antibody serology with a platform that allows the integration of control and elimination programs for different pathogens.